Multiple Distinctive Demyelinating Lesions Caused by Eosinophilic Granulomatosis With Polyangiitis: Case Report and Literature Review - Xu, Dingkang; Xu, Hongen; Wang, Fang; Wang, Guoqing; Wei, Qingjie; Lei, Shixiong; Gao, Qiang; Zhang, Qi; Guo, Fuyou (Frontiers in Neurology, 2019)
Eosinophilic granulomatosis with polyangiitis (EGPA) is an extremely rare rheumatic immune disease characterized by small- and medium-sized blood vessel vasculitis. Central nervous system (CNS) involvement frequently consists of cerebrovascular diseases, whereas a manifestation with multiple lesions and intracerebral occupying effects has never been reported. This report describes a 38-year-old man who presented with progressive deterioration of the memory and underwent microsurgery; EGPA was subsequently confirmed. Unique clinical and radiological features as well as immunohistological outcomes and DNA sequencing revealed a potential disease-associated HLA type, and single nucleotide polymorphisms (SNPs) are described for this uncommon case. Although EGPA rarely involves the CNS, this differential diagnosis should be considered when patients present with a history of nasosinusitis, elevated eosinophil percentage, clinical pulmonitis, and neurological manifestations. Microsurgery is necessary for precise diagnosis and effective treatment.